Patterns of better breast cancer care in countries with higher human development index and healthcare expenditure: Insights from GLOBOCAN 2020 - Azadnajafabad, Sina; Saeedi Moghaddam, Sahar; Mohammadi, Esmaeil; Delazar, Sina; Rashedi, Sina; Baradaran, Hamid Reza; Mansourian, Morteza (Frontiers in Public Health, 2023)
Background: The huge burden of breast cancer (BC) needs appropriate knowledge of the recent cancer epidemiology and quality of provided care. We aimed to evaluate BC epidemiology and quality of care, and to examine the impact of socioeconomic development and healthcare expenditure on BC care disparities. Methods: The results of the GLOBOCAN 2020 study were utilized to extract the data on female BC, including incidence and mortality numbers, crude rates, and age-standardized rates (ASIR and ASMR). Mortality-to-incidence ratio (MIR) was calculated for different locations and socioeconomic stratifications to examine the BC care disparities, as higher values of this ratio reflected poorer cancer quality of care and vice versa. The human development index (HDI) and the proportion of the current health expenditure from the gross domestic product (CHE/GDP%) were used to evaluate the MIR values in descriptive and analytic approaches. Results: Globally, 2 261 419 (95% UI: 2 244 260-2 278 710) new cases of female BC were diagnosed in 2020 with a crude rate of 58.5 per 100 000 population and caused 684 996 (675 493-694 633) deaths with a crude rate of 17.7. The World Health Organization Europe region had the highest BC ASIR (69.7), while Africa had the highest ASMR (19.1). The very high HDI category had the highest BC ASIR (75.6), and the highest ASMR was in low HDI areas (20.1). The global calculated value of female BC MIR in 2020 was 0.30, with the Africa region having the highest value (0.48) and the low HDI category (0.53). MIR and HDI values for countries/territories had a statistically significant strong inverse correlation (Pearson coefficient=-0.850, P-value<0.001). Also, MIR and CHE/GDP values showed a significant moderate inverse correlation (Pearson coefficient=-0.431, P-value<0.001). Conclusions: This study highlighted the higher MIR of BC in lesser developed areas and less wealthy countries. As an indicator of quality of care, MIR showed locations with higher health expenditure provide better care of BC. More focused interventions for developing regions and those with limited resources are needed to alleviate the BC burden and resolve cancer care disparities.